Letter from Éamonn Duggan to his fiancée May Kavanagh written during his detention in Lewes Prison, - Duggan, Éamonn, 1874-1936 (1917)
Duggan's letter, dated 31 March and 4 April 1917, is marked as being 'In lieu of a visit'. Writing to Kavanagh he refers to how much he values their relationship, how his recent experiences 'outrivals that of the greatest heroes of romantic fiction', his thoughts on Sean Connolly ('He died as he would have wished'), and his belief that the events of the last year will change him. Included is a brief note to his friend or relative Pauline. His letter is written on prison paper which outlines the rules governing prisoner's correspondence; Duggan signs himself as Edmund.